Development of web-based GIS for marine data information - Mahmud, Mohd. Razali; Zainal, Norfariza (2008)
Geographic Information System (GIS) is the main components in hydrography technology especially in navigation purpose. This paper summarizes the principal components of WebGIS and geodatabase for nautical chart providing map and data services. The term WebGIS or Webbased GIS denotes a type of Geographic Information System (GIS), whose client is implemented in a web browser. In addition, a web-based GIS facilitates and share the data globally, provide end-users a cost-saving solution to access and update spatial datasets from time to time if there are new changes identified. The data acquired is in vector format which it digitized from paper chart. Furthermore, a web-enable GIS based on ArcIMS (Internet Map Server) software was used which is extended to using ArcView as a tool to develop database, VBscript and ASP to customize the application.